1995
DOI: 10.1111/j.1467-9906.1995.tb00358.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Parents’ Involvement in Their Children’S Schooling

Abstract: This paper examines two dimensions of parental involvement with their children's schooling: (1) parent-child interaction with homework in the home and (2) parent-school staff interactions with meetings in the school. The data are drawn from an urban school district of 17,000 students, demographically reflecting many Northern central cities. The random sample consisted of 322 households with one or more children attending grades K-12 in the public schools. The data indicate a significant difference between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Correlations were grouped into those involving students in Grades 1 through 6, Grades 7 and 8, and Grades 9 through 12. One study (Smock & McCormick, 1995) was omitted from the analysis because it included students in Grades K through 12. Xu and Corno (2003) was also omitted from the analysis because it included students in Grades 6 through 8 and the correlation for the sixth graders could not be separated from that for the seventh and eighth graders.…”
Section: Resultsmentioning
confidence: 99%
“…Correlations were grouped into those involving students in Grades 1 through 6, Grades 7 and 8, and Grades 9 through 12. One study (Smock & McCormick, 1995) was omitted from the analysis because it included students in Grades K through 12. Xu and Corno (2003) was also omitted from the analysis because it included students in Grades 6 through 8 and the correlation for the sixth graders could not be separated from that for the seventh and eighth graders.…”
Section: Resultsmentioning
confidence: 99%
“…However, contrary to our hypotheses and prior research in low‐income samples (Fantuzzo et al., ; Grolnick, Benjet, Kurowski, & Apostoleris, ) in our sample married parents did not report higher home‐based or home‐school conferencing as compared to single or divorced parents. Importantly, other studies have not found a consistent association between family involvement and marital status (Fantuzzo et al., ; McWayne et al., ; Smock & McCormick, ). Again, given the ethnic and cultural diversity among the samples of low‐income families in these studies to date, as well as differences in the percentage of married parents across these samples, it is likely that these differences are sample specific and warrant further investigation.…”
Section: Discussionmentioning
confidence: 87%
“…Parent involvement in school life has become a central issue in the field of education, negotiated by parents, professionals, and politicians (Woods, 1988;Moore, 1992;Cibulka, 1996). Within the general debate over the restructuring of education, one finds a wide agreement concerning the benefits of such involvement (Moore, 1991;Fern, 1995;Black, 1993;Henderson and Berla, 1995;Smock and McCormick, 1995), regarded by some researchers as inevitable and critical (Woods, 1988). This view is supported by findings about the positive influence of parental involvement on children's academic accomplishments and communication skills, as well as on parents' and students' self-esteem and satisfaction with the children's schools (Griffith, 1996;Ryan, 1992;Henderson and Berla).…”
Section: Introductionmentioning
confidence: 99%